(Invited) Fully Porous GaN p-n Junctions Fabricated by Chemical Vapor Deposition: A Green Technology towards More Efficient LEDs. (13th April 2015) - Carvajal, Joan J.; Mena, Josue; Bilousov, Oleksandr; Martínez, Oscar; Jiménez, Juan; Zubialevich, V.Z.; Parbrook, Peter J.; Geaney, Hugh; O'Dwyer, Colm; Díaz, Francesc; Aguiló, Magdalena
Abstract : Porous GaN based LEDs produced by corrosion etching techniques have demonstrated enhanced light extraction efficiencies in the past. However, these fabrication techniques require further post-growth processing steps, which increase the price of the final device. In this paper, we review the process we developed for the formation of fully porous GaN p - n junctions directly during growth, using a sequential chemical vapor deposition (CVD) process to produce the different layers that form the p-n junction.